EXPERIENCE IN USE OF RECUPERATIVE BURNERS DEVICES IN FURNACES OF PERIODIC ACTION FOR HEAT TREATMENT OF BLANKS IN SPC-2 OJSC «BSW – MANAGEMENT COMPANY OF HOLDING «BMC» - D. S. Jadchenko (Литьë и металлургия)
In building and modernizing industrial furnaces the following important factors should be taken into account: on the one hand, economic efficiency must be ensured, and on the other hand it is important to reduce harmful emissions into the atmosphere, improve the working conditions of personnel, etc. At the same time, constantly increasing requirements for productivity and environmental friendliness should not adversely affect the period of cost recovery.This article considers the experience of using recuperative burners. Both positive and negative aspects of the use of burners are considered from the point of view of economics, ecology and technology.An important initial point of cost optimization is the correct choice of a heating system complete with an automatic control system. One example of an effective heating system is a burner with a built in air heating system (recuperative burner), which saves fuel, reduces harmful emissions and simultaneously improves the technical and economic performance of the furnaces.